Epidermal Cysts Masquerading as Steatocystoma Multiplex in the Vulva - A Rare Case Report - Gayathri M; Sharada RG; Sathyanarayanan R; Narasimhalu CRV; Vimal Chander R (Dr. Annil Mahajan, 2023)
Epidermal cysts are the most common benign cutaneous cysts derived from the follicular epithelium and most commonly occur over the face, trunk, extremities, and scalp. We report a 34-year-old female who presented to our outpatient department with multiple yellowish raised lesions over the genital region for 3 years associated with itching. On examination, multiple yellowish papules were noted over the vulva. On puncturing one of the cysts, yellowish cheesy material was seen. A provisional diagnosis of steatocystoma multiplex was considered based on the morphology of the lesions. Histopathological examination showed findings leaning towards the diagnosis of an epidermal cyst.